Вы находитесь на странице: 1из 5

PHYSICS 513: QUANTUM FIELD THEORY HOMEWORK 2 1

Physics 513, Quantum Field Theory


Homework 2
Due Tuesday, 16th September 2003
Jacob Lewis Bourjaily

1. a) Studying classical field theory, we derived the Euler-Lagrange equations of motion,


∂L ∂L
− ∂µ = 0.
∂φ ∂(∂µ φ)
It is trivial to show that a field which is described by the Lagrangian given has the following
equation of motion:
∂V
−m2 φ − − ∂µ ∂ µ φ = 0,
∂φ
¡ ¢ ∂V
=⇒ ∂µ ∂ µ + m2 φ = − . (1.1)
∂φ
Which is precisely the Klein-Gordon equation for a field in a potential V .
b) The canonical momentum is,
∂L
π= = ∂0 φ. (1.2)
∂(∂0 φ)
Using π, we write the Hamiltonian for the field.
Z Z
H = d3 xH = d3 x (π∂0 φ − L),
Z
¡ ¢
= d3 x π 2 − 1/2(∂0 φ)2 + 1/2(∇φ)2 + 1/2m2 φ2 + V (φ) ,
Z
1 ¡ ¢
= d3 x π 2 + (∇φ)2 + m2 φ2 + 2V (φ) . (1.3)
2
c) With a complex scalar field, the Lagrangian becomes
L = ∂µ φ∗ ∂ µ φ − m2 φ∗ φ − V (φ∗ φ).
Following the same procedure as in part (a) above, we use the Euler-Lagrange equation to
show that
∂V ∂V
−m2 φ∗ φ − φ∗ − φ ∗ − ∂µ φ∗ ∂ µ φ = 0.
∂φ ∂φ
¡ ¢ ∗ ∂V ∂V
=⇒ ∂µ ∂ + m φ φ = −φ∗
µ 2
−φ ∗ (1.4)
∂φ ∂φ
It is relatively easy to show that canonical momenta of the field are
∂L
π= = ∂0 φ∗ ;
∂(∂0 φ)
∂L
π∗ = = ∂0 φ.
∂(∂0 φ∗ )
Using this expression for π, we will proceed as above to compute the Hamiltonian.
Z Z
H = d xH = d3 x (π∂0 φ − L),
3

Z
¡ ¢
= d3 x π ∗ π − 1/2π ∗ π + 1/2∇φ∗ ∇φ + 1/2m2 φ∗ φ + V (φ∗ φ) ,
Z
1 ¡ ¢
= d3 x π ∗ π + ∇φ∗ ∇φ + m2 φ∗ φ + 2V (φ∗ φ) . (1.5)
2
2 JACOB LEWIS BOURJAILY

d) Let us derive the Noether current generated by a global phase rotation φ → φ0 = eiα φ. It
is clear that L0 = L because only modulus terms of φ appear in L. We rewrite the global
phase rotation to the first order as
φ → φ0 = eiα φ ≈ (1 + iα)φ ⇒ ∆φ = iφ;
φ∗ → φ0∗ = e−iα φ∗ ≈ (1 − iα)φ∗ ⇒ ∆φ∗ = −iφ∗ . (1.6)
We showed in class that the conserved Noether current associated with a symmetry is
specified by
∂L ∂L
jµ = ∆φ + ∆φ∗ ,
∂(∂µ φ) ∂(∂µ φ∗ )
= (iφ∂ µ φ∗ − iφ∗ ∂ µ φ) ,
= i (φ∂ µ φ∗ − φ∗ ∂ µ φ) . (1.7)
2. a) The Lagrangian for a source-free electromagnetic field is specified by
1
L = − Fµν F µν where Fµν = ∂µ Aν − ∂ν Aµ . (2.1)
4
It is clear that Fµν is antisymmetric, Fµν = −Fνµ . From our knowledge of the metric
tensor in Minkowski space, it is also clear that Fµν = −F µν if either µ or ν is zero and
Fµν = F µν if both µ and ν are nonzero. Because the field strength tensor is antisymmetric,
our calculation will be much easier.
1¡ ¢
L = − F01 F 01 + F02 F 02 + F03 F 03 + F12 F 12 + F13 F 13 + F23 F 23 ,
2
1¡ 2 2 2 2 2 2
¢
= F01 + F02 + F03 − F12 − F13 − F23 ,
2
1
= [(∂0 A1 − ∂1 A0 )2 + (∂0 A2 − ∂2 A0 )2 + (∂0 A3 − ∂3 A0 )2
2
− (∂1 A2 − ∂2 A1 )2 − (∂1 A3 − ∂3 A1 )2 − (∂2 A3 − ∂3 A2 )2 ],
1¡ 2 ¢
= E − B2 .
2
Now, let us try to find the Euler-Lagrange equations for motion for this field. Note that
from our work above if it clear that,
∂L
= 0.
∂Aν
After a short while of staring at the above equations, you should see that
½
∂L (∂µ Aν − ∂ν Aµ ) if µ = 0 or ν = 0,
=
∂(∂µ Aν ) −(∂µ Aν − ∂ν Aµ ) if µ, ν 6= 0,
µν νµ
= −F = F .
So the equations of motion are simply
∂µ F νµ = 0. (2.2)
i 0i ijk k ji
Knowing that E = −F and ² B = F , we can rewrite (2.2) as
0µ 0i
∂µ F = ∂i F = 0 = −∂1 E 1 − ∂2 E 2 − ∂3 E 3 = 0,
∴ ∇ · E = 0. (2.3)
The other equations also can be reduced to familiarity. Specifically,
∂µ F νµ = ∂µ F kµ = 0,
=⇒ ∂0 F k0 = ∂i F ki = ²ijk ∂i Bj ,
∴ ∇ × B = ∂0 E. (2.4)
These two equations represent half of Maxwell’s equations for a source-free field. The other
two equations relate the vector potential Aν with the E and B fields. These two other
equations were ‘given.’ We needed to know that B = ∇ × A and E = −∂0 A − ∇A0 to write
down the components of E and B in terms of Fµν .
PHYSICS 513: QUANTUM FIELD THEORY HOMEWORK 2 3

b) We construct the energy-momentum tensor, T µν , (using the equation derived in my unpub-


lished QFT notes),
∂L
T µν = ∂ν Aλ − Lδ µν , (2.5)
∂(∂µ Aλ )
It should be clear that by simply applying our results of part (a)
T µν = F λµ ∂ ν Aλ − Lδ µν .
This is not symmetric in µ and ν. Remember that the important aspect of T µν is that it is
conserved, i.e. ∂µ T µν = 0. To make T µν easier to work with, consider changing it to
T̂ µν = T µν + ∂λ K λµν .
Where K λµν is antisymmetric in its first two indices. By this antisymmetry, it is clear that
∂µ T̂ µν = ∂µ T µν + ∂µ ∂λ K λµν = 0.
So T̂ µν is a conserved quantity for any K λµν that is antisymmetric in its first two indices.
Let K λµν = F µλ Aν which is certainly antisymmetric in λ and µ because of F µλ . This
allows us to rewrite T̂ µν in a much simpler form. (Note the use of the Euler-Lagrange
equations to simplify line 2 below).
T̂ µν = T µν + ∂λ F µλ Aν ,
= T µν + Aν (∂λ F µλ ) + F µλ (∂λ Aν ),
= T µν + F µλ (∂λ Aν ),
= F λµ ∂ ν Aλ + F µλ ∂λ Aν − Lδ µν ,
= F λµ (∂ ν Aλ − ∂λ Aν ) − Lδ µν .
It should be clear that T̂ µν = T̂ νµ . Now we are ready to derive the Hamiltonian and total
momentum from T̂ µν . First, the Hamiltonian is
H = E = T̂ 00 ,
= E i (∂i A0 − ∂ 0 Ai ) − L,
1
= E2 − E i ∂ 0 Ai − (E2 − B2 ),
2
1 2
= (E + B2 ).
2
(2.6)
Note that in the last line of the derivation we had to set E i ∂ 0 Ai = 0. The total momentum
of the field is
S k = T 0k = −E i (∂ i Ak − ∂ k Ai ),
= Ei (∂ i Ak − ∂ k Ai ),
= Ei ijk Bk ,
∴ S = E × B. (2.7)
4 JACOB LEWIS BOURJAILY

3. a) The inner product, (f,g), will be defined


Z
(f, g) ≡ i d3 xf ∗ (x)∂0 g(x) − g(x)∂0 f ∗ (x),

We show that (f, g) is independent of time. This is demonstrated by direct computation.


Z
∂0 (f, g) = i d3 x∂0 [f ∗ (x)∂0 g(x) − g(x)∂0 f ∗ (x)],
Z
£ ¤
= i d3 x ∂0 f ∗ (x)∂0 g(x) + f ∗ (x)∂02 g(x) − g(x)∂02 f ∗ (x) − ∂0 f ∗ (x)∂0 g(x) ,
Z
£ ¤
= i d3 x f ∗ (x)∂02 g(x) − g(x)∂02 f ∗ (x) .

Using the Klein-Gordon equation, this reduces to


Z
∂0 (f, g) = i d3 xf ∗ (∇2 − m2 )g − g(∇2 − m2 )f ∗ ,
Z
= i d3 xf ∗ ∇2 g − g∇f ∗ .

We use Green’s Theorem to reduce the equation above to


Z
∂0 (f, g) = i (f ∗ ∇g − g∇f ∗ )~n · da = 0. (3.1)
S
The integral vanishes because we may assume that the fields go to zero at infinity.

b) Recall that the inverse Fourier transform of a Fourier transform of a function is the function
itself. Z · Z ¸
3 ikx d3 k −ikx
f (k) = d x e e f (k) .
(2π)3
Note that when we will express φ(x) in terms of ladder operators below, φ will be a function
of the 4-vectors k and x. There is a minus sign to keep track of that is different from the
book’s 3-vector representation.
Z
d3 k a ³ −ikx ´
φ(x) = 3
√ ak e + a†k eikx .
(2π) 2Ek
We are now ready to derive the required identity. It will proceed by direct calculation.
Z
ak = (fk (x), φ(x)) = i d3 x(f ∗ ∂0 φ − φ∂0 f ∗ ),
Z · Z
3 ikx d3 k 1 ³ −ikx † ikx
´
=i d x e −iE k ak e + iE k ak e
(2π)3 2Ek
Z 3 ³ ´ ¸
d k iEk
−eikx ak e−ikx + a†k eikx ,
(2π)3 2Ek
Z ·Z ´¸
3 ikx d3 k 1 ³ −ikx † ikx −ikx † ikx
= d xe ak e − ak e + ak e + ak e ,
(2π)3 2
Z Z
d3 k −ikx
= d3 xeikx e ak = ak ,
(2π)3
∴ ak = (fk (x), φ(x)) = ak . (3.2)
‘ ’
óπ²ρ ²́δ²ι δ²Äιξαι
PHYSICS 513: QUANTUM FIELD THEORY HOMEWORK 2 5
h i
c) Let us derive the the commutation relation ap , a†p0 = (2π)3 δ (3) (p − p0 ). To find this
commutation relation, we will first consider the fields in terms of ladder operators.
Z
d3 p 1
φ(x) = 3
p (ap + a†−p )eip·x ;
(2π) 2ωp
Z r
d3 p 0 ωp0 0
π(y) = (−i) (ap0 − a†−p0 )eip ·y .
(2π)3 2
Note that because the p’s are dummy variables, we cannot assume they are the same when
we “mix” the integration, so we have called one p’.
[φ(x), π(y)] = iδ (3) (x − y)
Z 3 3 0r
d pd p ωp0 −i ³ † † † † † † † †
´ 0
= 6
a p a p 0 − ap a
−p 0 + a−p a p0 − a
−p a −p 0 − ap 0 a p − a p0 a
−p + a−p0 ap + a−p 0 a−p ei(p·x+p ·y)
(2π) ωp 2
Z 3 3 0r
d pd p ωp0 i ³ † † † †
´ 0
= 6
a a
p −p 0 − a −p p
0 a + a 0 a
p −p − a −p pa 0 ei(p·x+p ·y) (cancelling like terms by symmetry)
(2π) ωp 2
Z 3 3 0r
d pd p ωp0 i ³h i h i´ 0
³ h i h i´
= 6
ap , a†−p0 + ap0 , a†−p ei(p·x+p ·y) note that ap , a†−p0 = ap0 , a†−p
(2π) ωp 2
Z 3 3 0r
d pd p ωp0 h †
i
i(p·x+p0 ·y)
= i a p , a −p 0 e = iδ (3) (x − y). (3.3)
(2π)6 ωp
Note that by the properties of the Dirac δ functional,
Z 3 3 0
d pd p i(p·x+p0 ·y)
ie = iδ (3) (x − y).
(2π)3
h i
Applying this knowledge to (3.3) from above, ap , a†−p0 must satisfy
Z 3 3 0r
d pd p ωp0
3
[ap , a†−p0 ] = 1.
(2π) ωp
This is identically satisfied if and only if we have that
h i
ap , a†−p0 = (2π)3 δ (3) (p + p0 ).
You can check this statement by noticing that this implies
Z 3 3 0r i rω
d pd p ωp0 h † p
a p −p0 =
, a = 1.
(2π)3 ωp ωp
Therefore, noting our use of −p, we may conclude that
h i
ap , a†p0 = (2π)3 δ (3) (p − p0 ) (3.4)

‘ ’
óπ²ρ ²́δ²ι δ²Äιξαι